Adsorption and rheological properties of acrylamide hydrogel - Kernosenko, L.A.; Nikovskaya, G.N.; Hodinchuk, N.V.; Panko, A.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
The interaction of various substances such as metals (in the form of cations, anions, organic complexes) and methylene blue (organic cationic dye) with hydrogel on the base of the copolymers of acrylamide and acrylic acid is studied. General regularities of the adsorption efficiency of these compounds by hydrogel and their rather low desorption are found. It is established that the positively charged sorbates show a better adsorption and a more slight desorption than negatively charged and uncharged substrates. Rheological experiments have shown that acrylamide hydrogel reveals a higher mechanical strength than natural soil and sand.